Innovazione tecnologica e sinergie tra soluzioni geospaziali Lo "scenario Intergraph" (Parte Seconda) - Fiduccia, Andrea (GEOmedia, 2012)
Continua in quest'articolo la descrizione delle soluzioni geospatial del nuovo scenario Intergraph che si sta delineando a seguito della fusione di molti player del settore della geomatica al'interno del gruppo Hexagon AB. La prima parte di questo articolo è stata pubblicata su GEOmedia 4/2011. Technological innovation and synergies between geospatial solutions. The "Intergraph's scenario". 2nd Part. In October 2010, Intergraph was acquired by and is now a wholly owned subsidiary of Hexagon AB. Hexagon is a lead-ing global provider of precision measurement technology sys-tems. Intergraph Security, Government & Infrastructure (SG&I) provides geospatially powered solutions to the public safety and security, defense and intelligence, government, trans-portation, utilities, and communications industries. Now since ERDAS is part of Intergraph, Intergraph provides integrated products for remote sensing, photogrammetry, and geospatial data management and delivery. Using Leica sensors and tech-nologies enhanced by Intergraph-ERDAS software technolo-gies, IMoSS (another company of HEXAGON AB) is a reliable partner when it is needed to monitor, analyse and visualise movements at millimetre level accuracy and to trasform the monitoring data into actionable intelligence.